Do Pro-Competition Healthcare Reforms Always Bring Health Benefits? Evidence from China - Zixuan Peng; Audrey Laporte; Xiaolin Wei; Jay Pan; Peter C. Coyte (Health Systems & Reform)
It is already a common practice for many health care systems in the world to opt for mixed markets where different types of health care facilities compete against each other to offer high-quality health care to patients. Nevertheless, little is known about the effects of the interaction between hospitals of the same or different type on patient health outcomes. This study estimated the impacts of aggregate and specific types of hospital competition by hospital-type on the quality of inpatient care using an analysis dataset comprising 267,183 individuals from China. The Herfindahl–Hirschman index was employed to measure the degree of hospital competition, with length of stay, readmission and mortality being used to measure the quality of inpatient care. The Poisson and binomial logistic models combined with the instrumental variable approach were constructed to estimate the impacts of hospital competition. This study generated three key findings: 1) aggregate hospital competition reduced the quality of inpatient care, as evidenced by a rise in the odds of readmission and length of stay; 2) intra-type hospital competition reduced the quality of inpatient care and in general had larger effects on reducing the quality of inpatient care than inter-type hospital competition; and 3) the only exception was in the way that competition between private nonprofit hospitals contributed to better quality of inpatient care. The overarching suggestion is that instead of treating competition as a panacea for improving health, a flexible plan tailored to specific conditions is needed.